1998
DOI: 10.1021/jf980527j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of Enantiomeric Pairs of Phosphosulfonate Herbicides

Abstract: The phosphosulfonates are a new class of soil-active herbicides which control a variety of annual grass and broadleaf weeds. Chirality at the phosphorus atom afforded the opportunity to explore stereospecific requirements for herbicidal activity. Chiral (hydroxymethyl)phosphinate intermediates were enzymatically resolved (Pseudomonas fluorescens lipase) from the racemic mixtures and then used to prepare two pairs of enantiomeric phosphosulfonates. Biological testing of the enantiomeric phosphosulfonate herbici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 16 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…Only a small fraction of them is manufactured and used in the form of a pure enantiomer [1]. The use of the pure enantiomer rather than the racemate causes less environmental damage because it avoids the unnecessary introduction of 50% of the pesticide into the environment [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Only a small fraction of them is manufactured and used in the form of a pure enantiomer [1]. The use of the pure enantiomer rather than the racemate causes less environmental damage because it avoids the unnecessary introduction of 50% of the pesticide into the environment [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Among various methods of their synthesis, the one based on the enzyme-promoted stereoselective transformations has become a subject of growing interest [1]. In this way, a series of optically active hydroxymethylphosphine oxides 1, interesting as precursors of herbicides [2], were synthesized by us using either their lipase-promoted acetylation (Scheme 1) or lipase-promoted hydrolysis of the O-acetyl derivatives 2, both performed under kinetic resolution conditions. Their absolute configurations were determined [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Biological testing of the enantiomeric phosphosulfonate herbicides demonstrated that the purified (+)-enantiomer is more active than the racemate (Spangler et al, 1999). Bialaphos, another organophosphorus herbicide, has carbon chiral centres, and its S-(+)-isomer is more active as a herbicide than its R-(-)-isomer.…”
Section: Other Chiral Herbicidesmentioning
confidence: 99%